2020
DOI: 10.1101/2020.05.22.20110544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Glucocorticoid Treatment in Sars-Cov-2 Infection Mortality: A Retrospective Controlled Cohort Study

Abstract: Objective: We aim to determine the impact of steroid use in COVID-19 pneumonia in-hospital mortality. Design: We performed a single-centre retrospective cohort study. Setting: A University hospital in Madrid, Spain, during March 2020. Participants: Patients admitted with SARS-CoV-2 pneumonia. Exposures: Patients treated with steroids were compared to patients not treated with steroids. A propensity-score for steroid treatment was developed. Different steroid regimens were also compared, and adjusted with a sec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
1
27
1
1
Order By: Relevance
“…Two of these studies found that patients treated with steroids had a lower prevalence of mechanical ventilation and shorter length of ICU and hospital stay than controls ( Fadel et al., 2020 ; Wang et al., 2020 ). In three other studies that only included COVID-19 patients with ARDS, the mortality rate was lower in patients treated with steroids than in controls ( Fernandez Cruz et al., 2020 ; Lu et al., 2020 ; Wu et al., 2020 ). In COVID-19 patients treated with tocilizumab, additional administration of steroids was also associated with a lower mortality rate ( Sanz Herrero et al., 2020 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Two of these studies found that patients treated with steroids had a lower prevalence of mechanical ventilation and shorter length of ICU and hospital stay than controls ( Fadel et al., 2020 ; Wang et al., 2020 ). In three other studies that only included COVID-19 patients with ARDS, the mortality rate was lower in patients treated with steroids than in controls ( Fernandez Cruz et al., 2020 ; Lu et al., 2020 ; Wu et al., 2020 ). In COVID-19 patients treated with tocilizumab, additional administration of steroids was also associated with a lower mortality rate ( Sanz Herrero et al., 2020 ).…”
Section: Resultsmentioning
confidence: 91%
“…Six retrospective cohort studies also found that the use of steroids was associated with beneficial outcomes in patients with COVID-19 ( Fadel et al., 2020 ; Fernandez Cruz et al., 2020 ; Lu et al., 2020 ; Sanz Herrero et al., 2020 ; Wang Y. et al., 2020 ; Wu et al., 2020 ). Two of these studies found that patients treated with steroids had a lower prevalence of mechanical ventilation and shorter length of ICU and hospital stay than controls ( Fadel et al., 2020 ; Wang et al., 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…A retrospective cohort analysis of patients with COVID-19 who developed ARDS (41.8% of patients) showed that treatment with methylprednisolone was associated with a decreased risk of death (HR 0.38; 95% CI 0.20–0.72) [ 80 ]. A single-center retrospective cohort study reported that hospitalized COVID-19 patients treated with steroids ( n = 396) had a lower mortality rate than those who did not receive steroids ( n = 67), 13.9% vs. 23.9% (HR 0.51, 95% CI 0.27–0.96, p = 0.044) [ 81 ]. The recently published Randomized Evaluation of COVID-19 Therapy (RECOVERY) trial, an open label randomized controlled trial compering dexamethasone (6 mg daily for 10 days) versus standard of care, terminated enrollment early due to a mortality benefit with dexamethasone [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…4). Sensitivity assessment done after excluding a study with significantly high weight (Cruz AF 2020 [25]) showed significant odds for getting corticosteroids among ARDS (OR 5.64, 95% CI 2.02 to 15.70) (Additional file 4/ Fig. 5).…”
Section: Sensitivity Analysismentioning
confidence: 99%